Patent toxicity - Gianluca Biggi; Elisa Giuliani; Arianna Martinelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
A toxic-free world is one of the goals of the European Green Deal and a key objective of the World Health Organization Inter-Organization Programme for the Sound Management of Chemicals. However, although use of some toxic chemicals is being banned, others continue to be developed. We consider this motivation for a closer examination of the toxicity of chemical inventions. We combine patent analysis with computational toxicology and develop a methodological roadmap to measure patent toxicity, that is, the extent to which a patent includes 'components' (or compounds) that are toxic to humans and/or the environment. To illustrate our proposed methodology, we analyse the toxicity of ten well-known hazardous chemicals. The measurement of patent toxicity opens up interesting avenues for future research and, potentially, has some strong policy implications.
Keywords: O3; L65; 330; Patents; computational toxicology; chemical inventions